2003
DOI: 10.1634/stemcells.21-4-389
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to Utilize Mesenchymal Progenitor Cells as Cellular Vehicles

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
104
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(107 citation statements)
references
References 46 publications
2
104
0
1
Order By: Relevance
“…In particular, transduction of MSC with adenoviral vectors seems relatively inefficient compared with LV gene transfer, which is at least partly a result of the limited expression of the cellular coxsackie and adenovirus receptor on the MSC. 11,50 In addition, unlike LV vectors, adenoviral vectors do not integrate in a typically dividing MSC cell population. Consequently, the potentially therapeutic transgene is diluted over time, limiting the use of adenoviral vectors to gene therapy of disorders that would benefit only from short-term expression of a potentially therapeutic transgene in MSC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, transduction of MSC with adenoviral vectors seems relatively inefficient compared with LV gene transfer, which is at least partly a result of the limited expression of the cellular coxsackie and adenovirus receptor on the MSC. 11,50 In addition, unlike LV vectors, adenoviral vectors do not integrate in a typically dividing MSC cell population. Consequently, the potentially therapeutic transgene is diluted over time, limiting the use of adenoviral vectors to gene therapy of disorders that would benefit only from short-term expression of a potentially therapeutic transgene in MSC.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in studying MSC biology have shown that this cell population exhibits some properties that suggest the feasibility of their use as a cellular vehicle: a relative simple isolation method, the ability to be cultured in vitro and to expand to quantities required for therapy, the ability for ex vivo transduction with viral vectors, plasticity, the potential to differentiate under exogenous stimuli, high metabolic activity, an efficient machinery to express therapeutic proteins and the ability to be delivered systemically or locally. 11 A highly efficient gene transfer method is needed to circumvent the need for selective enrichment and long-term culture of MSC that may contribute to senescence or compromise multipotency. 12 This justifies the use of lentiviral vectors (LV) for transducing MSC by virtue of their ability to transduce both dividing and non-dividing cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies of CRAd-loaded carrier cells, mesenchymal stem cells have often been used as carrier cells, and fiber-mutant CRAds have been used for efficient infection of mesenchymal stem cells, leading to efficient preparation of CRAd-loaded carrier cells, because mesenchymal stem cells poorly express CAR, which is the primary receptor for Ad5. 30,31 Our group has previously demonstrated that human and mouse mesenchymal stem cells are less efficiently transduced with conventional Ad vectors, but that fiber-mutant Ad vectors, including an Ad vector containing the RGD (Arg-Gly-Asp) peptide and the poly-lysine peptide in the HI loop and the C-terminus of the fiber knob, respectively, and a fibersubstituted Ad vector showing the fiber protein of Ad35, efficiently transduce mesenchymal stem cells. 32,33 Mesenchymal stem cell-based carrier cells loaded with fibermutant CRAds mediate efficient antitumor effects; however, it has remained unclear whether use of a fibermutant or fiber-substituted CRAd is crucial for not only efficient preparation of carrier cells but also efficient killing of CAR-negative tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…54,55 A major advantage of MPCs is that they are readily available from healthy donors and can be expanded quickly in cell culture. 61 Therefore, it can be suggested that MPCs have the potential to serve as cell carriers for the treatment of MM, since these cells are derived from the bone marrow and travel via the blood vessels.…”
Section: Mesenchymal Progenitor Cellsmentioning
confidence: 99%